2003
DOI: 10.1046/j.1445-2197.2003.t01-14-.x
|View full text |Cite
|
Sign up to set email alerts
|

Boerhaave's syndrome: 10 years experience and review of the literature

Abstract: Boerhaave's syndrome is rare and its management is not uniform. A review of the literature demonstrates wide disparity in management due to the rarity of the condition. Primary repair is appropriate for ruptures diagnosed early. Many are diagnosed late and T-tube drainage may be the simplest way to manage this difficult condition in this situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 11 publications
1
24
0
4
Order By: Relevance
“…This feature is observed in about 90% of the cases (1)(2)(3)8,(11)(12)(13)(14). The mucosal injury is usually longer and extends beyond the muscular tear, and this has important implication for the technical aspects of the repair (14,15). The mediastinum and often one or both pleural cavities become thus infected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This feature is observed in about 90% of the cases (1)(2)(3)8,(11)(12)(13)(14). The mucosal injury is usually longer and extends beyond the muscular tear, and this has important implication for the technical aspects of the repair (14,15). The mediastinum and often one or both pleural cavities become thus infected.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrition is an important aspect of treatment in patients presenting with esophageal perforation therefore, besides primary esophageal repair drainage gastrostomy and above all feeding jejunostomy are useful adjunctive options that should be strongly considered during the operative procedure (3,6,11,14,16,17,25,28). In our study, adequate nutritional support was performed through a nasal feeding tube or a jejunostomy in all cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hill et al found an approximate incidence of one in 53,000 of all hospital admissions. 2 Spontaneous esophageal ruptures are less common than iatrogenic and traumatic esophageal ruptures, and account for 15-40% of all esophageal perforations. [3][4][5][6] Boerhaave syndrome usually occurs in patients 40 -60 years old, but has also been reported in neonates and the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…In approximately 90% of the cases, the area of perforation and contrast leak is at the left posterolateral aspect of the distal third of the oesophagus, usually within 2-3 cm above the oesophagogastric junction. 8 The complication risk of endoscopic assessment (OGD) is minimal and it excludes the diagnosis if normal. It also influences the management if underlying pathology, such as cancer is found and facilitates placement of nasojejunal feeding tube if required.…”
mentioning
confidence: 99%